Records Management in Support of Administrative Effectiveness at PT Sankyu International Indonesia - Shafa Salsabila; Herry Sutanto (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Records management plays a fundamental role in supporting administrative effectiveness and ensuring the continuity of organizational operations. This study examines records management practices at PT Sankyu International Indonesia, a company operating in the construction and engineering services sector. Employing a descriptive qualitative approach, data were collected through participant observation during an internship program, interviews with administrative personnel, and analysis of organizational documents. The study focuses on records creation, classification, storage, retrieval, maintenance, and disposition, as well as their contribution to administrative effectiveness. The findings reveal that the company has implemented a structured records management system integrating physical and digital archives. Such practices facilitate information accessibility, improve document retrieval efficiency, strengthen interdepartmental coordination, and support administrative decision-making processes. The study also highlights the growing contribution of digital archiving in enhancing administrative performance through improved information security, storage efficiency, and operational responsiveness. These findings demonstrate that effective records management functions as an important organizational mechanism for supporting administrative effectiveness within a project-based business environment.